Development of Raman acousto-optic frequency shifter based on SAW - 王春梅 温志渝 张祖伟 张颖异 (Journal of semiconductors, 2014)
A Raman acousto-optic frequency shifter （AOFS） based on surface acoustic wave （SAW） is presented. It consists of a double-ended SAW resonator and optical waveguide system. The structure parameters of the SAW resonator are optimized using COM software and the optical waveguide system is designed using an effective index method. The AOFS prototype fabricated using MEMS technology is detected. The optical beat signals su- perimposed by ± 1st-order and ±2nd-order diffracted beams are detected. The frequency shift of 78.2201 MHz related to the 1 st-order diffracted beams and 156.2306 MHz related to the 2nd-order diffracted beams are obtained respectively.